A Critical Systematic Literature Review of Global Inclusive Education Using an Affective, Intersectional, Discursive, Emotive and Material Lens - David Isaac Hernández-Saca; Catherine Kramarczuk Voulgarides; Susan Larson Etscheidt (MDPI AG, 2023)
We conducted a critical systematic literature review on global inclusive education and law. The critical review questions were: (1) how have scholars theorized, conceptualized, and studied global inclusive education? (2) How do scholars define global inclusive education? (3) And what do scholars cite as prominent international inclusive education law? We ask such questions given the ongoing global crises that situate historically marginalized groups in even more precarious positions-including students with dis/Abilities. Given this framing, we employed a critical systematic literature review that is cognizant of our positionalities, writing from the Global North, so that we can identify lines of inquiry related to global inclusive education that can disrupt global cultural hegemony. Global inclusive education was defined broadly from access to employment through a human right, systemic change, academic, social and emotional frameworks for students with dis/Abilities' inclusion of all "regardless" of markers of difference. International inclusive education law was approached by affirming the aspirational visions of numerous United Nations' conventions and policies that focused on social justice for Black, Indigenous and Youth of Color with dis/Abilities in education and global society, without necessarily accounting for the interactions between how macro (legal), meso (local contexts) and micro (student voices) are or are not considered in the global inclusive space.